1987
DOI: 10.1038/327059a0
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant-free IgG responses induced with antigen coupled to antibodies against class II MHC

Abstract: The generation of strong serological responses to protein antigens in experimental animals usually requires the use of potent adjuvants, most of which cannot be used in human or veterinary vaccines because of deleterious side effects. Attempting to circumvent this problem, we have assessed an adjuvant-free antigen-delivery system based on the hypothesis that antigen coupled to monoclonal antibodies (mAbs) specific for class II major histocompatibility complex (MHC) determinants should be 'targeted' onto antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 0 publications
5
75
0
Order By: Relevance
“…5 and 6). At different times after immunization, the effectiveness of priming was assessed in two ways (1). Transgenic cells in the inguinal LN (after s.c. injection) or spleen (after i.v.…”
Section: Differential Stimulation Of Cd4 ϩ and Cd8 ϩ T Cells By Targementioning
confidence: 99%
See 1 more Smart Citation
“…5 and 6). At different times after immunization, the effectiveness of priming was assessed in two ways (1). Transgenic cells in the inguinal LN (after s.c. injection) or spleen (after i.v.…”
Section: Differential Stimulation Of Cd4 ϩ and Cd8 ϩ T Cells By Targementioning
confidence: 99%
“…One of these is vaccination, the efficiency of which can be enhanced by optimizing Ag delivery to DCs. This can be done by using Abs specific for DC-expressed molecules as in vivo Ag carriers; using such an approach, a lowered requirement for Ag dose in stimulating immune responses in mice has been observed after targeting a variety of molecules, including MHC class II, CD11c, CD205, CD80/86, F4/80-like receptor (FIRE), CIRE, and the undefined Ag recognized by the mAb 33D1 (1)(2)(3)(4)(5)(6)(7)(8)(9). In addition, in vitro studies have shown that Abs specific for the mannose receptor or DC-SIGN can effectively deliver Ag to human DCs, indicating that this strategy will also be applicable to human vaccination (10,11).…”
mentioning
confidence: 99%
“…CD4 ϩ T cells mainly recognize peptides derived from the processing of extracellular antigens by antigen-presenting cells (APCs), presented in association with MHC class II molecules. Targeting of antigen to APCs by coupling to APC-specific Abs increases CD4 ϩ T cell activation, probably because of increased uptake of antigen (3,4).…”
mentioning
confidence: 99%
“…Thus, sustained Ag presentation, as is the case in the repeated administration of protein therapeutics, may lead to effective T cell activation and differentiation (35). Furthermore, the targeting of specific receptors on APCs even in the absence of proinflammatory signals may generate efficient Ab responses (36).…”
Section: Professional Apcs Are the First Immune-sensitive Depots For mentioning
confidence: 99%